Efektivitas Sidang Keliling Pengadilan Agama Sampit Dalam Penyelesaian Perkara Hukum Keluarga - Hidayatullah, Muhammad Zaki (LP2M IAIN Palangka Raya, 2016)
Research conducted by the researchers focused on three things. First, how the background of the idea of the circuit court of the Religious Courts Sampit. Second, what is the basic provisions that allow a circuit court Sampit Religious Court. Third, how the effectiveness of the implementation of the circuit court Sampit Religious Court. This research is the study of law (legal research) is research that uses the type of sociology of law studies with persefektif EMIC. Using descriptive qualitative approach and a sociological approach to examine perceptions and behaviors that occur in the field of law. The data used in this study of primary data and secondary data. Subjects in this study there are 8 (eight) that three judges Religious Court Sampit, clerks replacement Religious Court Sampit, bailiff Religious Court Sampit, cashier/administration Religious Court Sampit, head of the Religious Affairs Office District of Seruyan Hilir Seruyan, head of the Religious Affairs Office Subdistrict Katingan Katingan Hilir district and subdistrict head of the Religious Affairs Office of the Middle Katingan Katingan. Collecting data through interviews, observation, documentation and to pengabsahannya through source triangulation techniques. Meanwhile, the data analysis through three stages, namely data reduction, display data, and Conclusion. These results indicate that the background for the circuit court in the Religious Sampit three factors. First, the distance is quite far away. Second, geographical location or terrain traveled not only by land but there are also passing through the waterway. Third, to facilitate justice seekers get justice in the legal field. The legal basis that allows the circuit court Sampit Religious Court that the Supreme Court Circular (SEMA) No. 10 Year 2010 on Guidelines for Providing Legal Aid, gave an order from the High Court of Religion and Government Contracting Palangkaraya East Kotawaringin with DIPA funds given to the implementation of circuit courts Operational costs. While the effectiveness of the implementation circuit court conducted Religious Courts Sampit runs well and is very effective for society. The procedural law is used also law applicable in ordinary proceedings (litigation regular), which differ only in their implementation outside the Religious Court Sampit, namely in the Religious Affairs Office (KUA) local.